Formulation and Determination of the Strengths, Weaknesses, Threats, and Opportunities Governing Swimming in Iraq - Jabbar Nadoush Nasir , Ali; Azizian Kohan, Nasrin; Naghizadeh Baghi , Abbas; Moharramzadeh , Mehrdad (Journal of Foresight and Health Governance, 2026)
The present study aimed to formulate and determine the strengths, weaknesses, opportunities, and threats governing children’s swimming in Iraq in order to provide practical strategies for the development of this fundamental and medal-winning sport. This applied descriptive-analytical study included sport managers, coaches, young swimmers, and physical education students in Iraq. A total of 134 participants were selected purposively. Data were collected through documentary studies, expert interviews, and a researcher-made questionnaire. The face and content validity of the questionnaire were confirmed, and its reliability, measured by Cronbach’s alpha, ranged from 0.85 to 0.92. Descriptive statistics, the Friedman test, Internal and External Factor Evaluation matrices, the Internal-External matrix, and SWOT analysis were used for data analysis. The results showed a significant difference among the four SWOT factors. The most important strengths included the existence of educational institutions related to physical education, the presence of specialized sport managers, and the existence of talented children and adolescents. The most important weaknesses included insufficient attention to children’s needs and interests, limited access to standard facilities, and lack of financial resources. The existence of potential talents, increased participation of children in sport activities, and expansion of sport events were identified as the most important opportunities. In addition, the increased cost of swimming pool maintenance, the rising price of equipment, and children’s tendency toward sedentary leisure activities were among the most important threats. Based on SWOT analysis, 11 strategies were formulated in four groups: aggressive, competitive, conservative, and defensive. The development of children’s swimming in Iraq requires strategic planning, coordination among sport and educational institutions, sustainable investment, and serious attention to children’s age-related needs. It is suggested that establishing an integrated talent identification system, training specialized coaches, and standardizing equipment and swimming pools for children should be prioritized in executive programs.